Pengaruh Proporsi Direksi Independen, Proporsi Komisaris Independen Dan Stakeholders Terhadap Sustainability Report - Michael, Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to obtain empirical evidence about proportion of independent director, proportion of independent commissioner, environment and employee on the sustainability report in the banking in the period of 2013-2016. The research is conducted by taking sample of 14 banking industries using purposive sampling method. The result of this research shows that all the independent variables have effects on earning management simultaneously (F test). The t test shows that proportion of independent director, environmental and employee have no significant effect on earnings management, while proportion of independent commissioner has the significant negative effect sustainability report. For the further research, it is recommended to use guidelines that apply during the period of research so that research can be in accordance with the actual conditions